Literacy Skills as an Effort to Maintain Quality Culture in Muhammadiyah Elementary Schools in Malang City During the Covid-19 Pandemic - Poerwanti, Endang; Suwandayani, Beti Istanti; Sombuling, Agnis (Universitas Negeri Semarang, 2021)
This research has been conducted based on the declining condition of literacy in Indonesia since 2017. Since quality culture is crucial during this time, a research on literacy skills in elementary schools needs to be done. This is a qualitative descriptive research. It aims to analyze the literacy skills in maintaining the quality culture in Muhammadiyah elementary schools in Malang City during the Covid-19 pandemic. Moreover, the instruments used in this research are interviews and documentation. The research subjects comprise teachers, headmasters, and students of Muhammadiyah elementary schools in Malang City. The results show that during the pandemic, the subjects have applied digital and informational literacy skills in the learning process through several platforms. Moreover, using these skills, the teachers have co-written a compilation of best practic-es registered on ISBN. Supporting factors in literacy skills as a quality culture in Muhammadiyah elementary schools include the intensity to access more information, optimization of teacher skills through various workshops and peer tutors, and improvement of existing infrastructure in schools. While the hindering factor is the understanding of educators and education on the school literacy movement is school literacy.